2021
DOI: 10.3390/app11167258
|View full text |Cite
|
Sign up to set email alerts
|

Drift Evaluation of a Quadrotor Unmanned Aerial Vehicle (UAV) Sprayer: Effect of Liquid Pressure and Wind Speed on Drift Potential Based on Wind Tunnel Test

Abstract: Background: Unmanned Aerial Vehicles (UAVs) applied to agricultural plant protection is widely used, and the field of operation is expanding due to their high efficiency and pesticide application reduction. However, the work on pesticide drift lags behind the development of the UAV spraying device. Methods: We compared the spray drift potential at four liquid pressures of 2, 3, 4, and 5 bar ejected from the hydraulic nozzles mounted on a UAV test platform exposed to different wind speeds of 2, 4, and 6 m/s pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
(40 reference statements)
1
6
0
2
Order By: Relevance
“…In addition, the test platform can adjust the pitch angle from –30 ° to 30 ° . Liu et al (2021) combined the UASS platform with the wind tunnel and placed the platform at the extremity of the wind tunnel in order to build an indoor drift test device. Although the sampling area is not located inside the wind tunnel, this method is a good attempt to reduce disturbances from natural environmental conditions.…”
Section: Characteristics Of Unmanned Aerial Spraying Systems and Spra...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the test platform can adjust the pitch angle from –30 ° to 30 ° . Liu et al (2021) combined the UASS platform with the wind tunnel and placed the platform at the extremity of the wind tunnel in order to build an indoor drift test device. Although the sampling area is not located inside the wind tunnel, this method is a good attempt to reduce disturbances from natural environmental conditions.…”
Section: Characteristics Of Unmanned Aerial Spraying Systems and Spra...mentioning
confidence: 99%
“…On one hand, the operating efficiency of a single UASS has increased from 2 to 3 hectares per hour to the current 15–20 hectares per hour within the past 5 years ( Chen H. et al, 2021 ). The result of single-machine efficiency implies that more chemicals can be sprayed in a short time ( Wang Z. et al, 2022 ), however more pesticide droplets may also be scattered in the air ( Liu et al, 2021 ). The overall environmental risks due to efficiency improvements need to be assessed.…”
Section: Introductionmentioning
confidence: 99%
“… Ferguson et al (2016) applied three different pressures of 207, 310, and 414 kPa to five types of nozzles and found that the number density of droplets is affected by pressure, with higher pressure leading to the largest density. Liu et al (2021) performed experiments on the liquid distribution performance of a nozzle under four pressures. The experimental results showed that when the pressure was adjusted from 200 to 500 kPa, the value of Dv0.5 ranged from 124.46 to 85.95 μm, and when 400 or 500 kPa liquid was used, the droplets size distribution was more uniform.…”
Section: Unmanned Aerial Vehicle Operation Parameters Affecting the D...mentioning
confidence: 99%
“…Embora as máquinas agrícolas terrestres desempenhem um papel fundamental na pulverização das lavouras, áreas agrícolas íngremes e montanhosas ou culturas de alto porte, restringem sua utilização no controle de doenças, pragas e plantas daninhas (GUO et al, 2020;LAN;CHEN, 2018;WANG et al, 2022a). As aeronaves tripuladas mesmo que equipadas com tecnologia avançada de pulverização, ainda apresentam limitações de uso, como o elevado risco de deriva (LIU et al, 2021a).…”
Section: Introdução Geralunclassified
“…A velocidade de voo (CHEN et al, 2017;, o volume de calda (CHEN et al, 2018;, a altura de voo (BAE; KOO, 2013; e as pontas de pulverizações mais adequadas ainda são importantes fatores de estudo nesse tipo de pulverização (CHEN et al, 2020a(CHEN et al, , 2020bFAN;. A quantidade de deriva gerada nas aplicações com VANTs também tem sido pesquisadas (GUO et al, 2020;LIU et al, 2021a;TANG et al, 2017;YU et al, 2021). Esses estudos vêm sendo desenvolvidos tanto em cultivos de baixo porte (WANG et al, 2022b;YAN et al, 2021;ZHAO et al, 2022) como em culturas arbóreas .…”
Section: Introdução Geralunclassified